2003
DOI: 10.1097/00004770-200304000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Concentrations of Sodium Hypochlorite on the Ability of MTAD to Remove the Smear Layer

Abstract: Various organic acids, ultrasonic instruments, and lasers have been used to remove the smear layer from the surface of instrumented root canals. The purpose of this study was to investigate the effect of various concentrations of sodium hypochlorite (NaOCl) as an intracanal irrigant before the use of MTAD (a mixture of a tetracycline isomer, an acid, and a detergent) as a final rise to remove the smear layer. Ten operators, using a combination of passive step-back and rotary 0.04 taper, nickel-titanium files, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
185
1
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(221 citation statements)
references
References 15 publications
20
185
1
15
Order By: Relevance
“…Subsequent in vitro experiments showed that this material effectively removed the smear layer. 71 When the antimicrobial effects of MTAD were compared with those of NaOCl and EDTA by using standard in vitro microbiological techniques, MTAD was significantly more effective; 46 however, these effects have recently been challenged by different investigators. Ruff et al 72 reported superior antifungal effect of 6% NaOCl and 2% chlorhexidine compared with MTAD, and Clegg et al 73 questioned the ability of MTAD to remove or disrupt bacterial biofilms in root canals.…”
Section: Future Development In Root Canal Irrigationmentioning
confidence: 99%
“…Subsequent in vitro experiments showed that this material effectively removed the smear layer. 71 When the antimicrobial effects of MTAD were compared with those of NaOCl and EDTA by using standard in vitro microbiological techniques, MTAD was significantly more effective; 46 however, these effects have recently been challenged by different investigators. Ruff et al 72 reported superior antifungal effect of 6% NaOCl and 2% chlorhexidine compared with MTAD, and Clegg et al 73 questioned the ability of MTAD to remove or disrupt bacterial biofilms in root canals.…”
Section: Future Development In Root Canal Irrigationmentioning
confidence: 99%
“…This may be explained by the reduced amount of irrigation solution contained in a smaller canal volume [22][23][24] . Additionally, in the coronal part of the root canal, more chelator molecules are able to bind calcium ions [25][26][27] because of the larger canal volume at this part.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that citric acid or a combination of NaOCl and citric acid irrespective of the order in which they were used was more effective than NaOCl alone to remove the smear layer from the surface of instrumented canals. Because high concentrations of NaOCl are more toxic than diluted solutions and there are no significant differences between the ability of 1.3%, 2.6% and 5.25% as root canal irrigants and MTAD as a final rinse to remove the smear layer 22) , 1.3% NaOCl during instrumentation and MTAD as a final rinse was used to remove the smear layer in Group 5.…”
Section: ⅳ Discussionmentioning
confidence: 99%